Knowing heaven astronomy, the calendar, and the sagecraft of science in early imperial China - Morgan, Daniel P. (University of Chicago, Division of the Humanities, Department of East Asian Languages and Civilizations, 2013)
This dissertation is a series of textual case studies on nontraditional sources for li calendro-astronomy" circa 250 BCE - 250 CE: (1) the silk manuscript guide to military planetary astronomy/astrology Wuxing zhan (168 BCE), (2) excavated calendars and state li manuals, and (3) the Jin shu's record of the debate surrounding a failed attempt at li reform in 226 CE. This selection affords us a number of unique cross sections through the astral sciences. Balancing transmitted with excavated sources, I emphasize realia and their perspective on era technical knowledge, the formats in which it was produced and consumed, and its transmission and practice beyond an elite court-centered context. In addition to the three elements of li--calendrics, eclipses, and planetary astronomy--my selection draws together the broad array of astral sciences, exploring distinctions in genre, sociology, and epistemology between, for example, mathematical astronomy, hemerology, and omenology, and the (tortuous) processes by which knowledge moved between them. Each chapter also juxtaposes the normative descriptions of manual literature with products of practice--tables, calendars, and test results--to reflect upon the distance between them and, thus, the limitations of the former as historical testimony. Across these cross sections, my study focuses on the question of empiricism and progress. I foreground these topics not because they define twentieth-century notions of science but because, as I argue, they define early imperial notions of li--a point that our twenty-first-century aversion to positivism and Whig history tends to obscure. To this end, I catalog the conceptual vocabulary of observation and testing, submit empirical practices to mathematical and sociological analysis, and, most importantly, explore the formation and function of legend--the histories of science that early imperial actors wrote and recounted in their own day
Keywords: Hochschulschrift